The Effectiveness Of Elsa Speak Application To Improve Speaking Skill In Extra Class - Bahtiar, Yuyun; Sa’diyah, Lailatus; Agustina, Ulfa Wulan; Nur, Luluk Choirun Nisak; Ma’arif, Iin Baroroh (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This study aims to test the effectiveness of the Elsa Speak application as a learning medium in improving English speaking skills of additional class students at Al-Bairuny Islamic School. The researcher used a quasi-experimental design with two groups: an experimental group taught using the AI-based Elsa Speak application and a control group taught without the application. The results showed a significant increase in the experimental group's speaking skills, especially in pronunciation, fluency, and confidence. The control group only showed minimal improvement. These findings indicate that Elsa Speak, as an AI-based learning medium, is effective in improving students' English speaking skills. This study shows the importance of using AI-based technology in language learning to improve the quality of English education in the digital era.